Efectos de la producción nacional y la confianza en SUNAT en la recaudación de tributos internos en Perú 2014 – 2023 - Rodriguez Vargas, Rolando Christian Bill (2024)
Internal tax collection is the amount of income obtained from the collection of taxes and mandatory contributions managed by SUNAT. These include income, production and consumption taxes, as well as other tax revenues. Thus, this research provides data on the effects of national production and trust in SUNAT, on the collection of internal taxes in Peru during the period from the first quarter of 2014 to the third quarter of 2023. Adopting a Quantitative and causal with a non-experimental design of longitudinal data, the research determined that, as national production grows by 1%, the collection of internal taxes will grow by 1,135% during the same period. Otherwise, no significant effect of trust in SUNAT was identified on the collection of internal taxes in Peru 2014-2023. Finally, it was identified that the independent variables, together, explain 75.84% of the variations in internal tax collection during the period analyzed.